Application of Information Technology for Enhancing Accounting Effectiveness in the Regional Finance and Assets Agency - Sudarti; Hasniaty; Abd. Samad; Makungu Paschal (Invoice : Jurnal Ilmu Akuntansi, 2025)
Purpose: This study aims to evaluate the effectiveness of the Regional Government Information System (SIPD) in improving efficiency, transparency, and accountability in regional financial management, with a focus on identifying the factors that hinder its optimal implementation at the Regional Financial and Asset Agency (BKAD) of Paniai Regency. Design/Methodology/Approach: A qualitative research design was employed using in-depth interviews and document analysis. Informants included one division head, three financial staff members, and two IT personnel at BKAD. Data were analyzed using thematic analysis to identify major challenges and recurring themes related to SIPD implementation. Findings: The study reveals that SIPD implementation is constrained by several challenges, including limited internet connectivity in remote areas, inadequate technological infrastructure, and insufficient human resources with the necessary technical expertise. Additionally, poor synchronization between BKAD and other regional government agencies (OPDs) in financial reporting contributes to delays in the preparation of financial statements. Practical Implications: The findings suggest that enhancing technological infrastructure, procuring compatible devices, and providing targeted training programs are crucial to improving system performance. Furthermore, strengthening regulations and policies is necessary to ensure compliance and inter-agency coordination. Originality/Value: This study contributes to the literature by offering empirical insights into SIPD implementation challenges in an under-researched region, providing actionable recommendations for policymakers and practitioners to enhance financial transparency and accountability.